Energy management system - Nuraini, Ahmad Ariff Shah (2009)
This project report describes the design and implementation of the computer system Home Energy Management System. The system provides a user the ability to differentiate between and limit the use of major power consuming appliances, allowing them to save energy and monitoring power usage at home. This system is developed to manage the power consumption in daily life. By creating this system the power usage will be consume wisely without any waste. This system control or limited the power consumption by turn off the electrical appliance when the amounts of power consumption exceed the limit. The user can set the desired amount of power usage in daily in order to save power consumption. It also allows the user to see the consumption rate for difference appliance in their house by monitor power consumption on LCD display. Buttons are used to select which parameter (voltage. current and power consumption) to be monitored. The system required three main parts include on hardware and software which is power source, controlling unit and monitoring system. The system used as PIC16F877A as a controller and ADE7753 where offer measured analog voltage and current input. The analog inputs are sample by ADC within the ADE7753, and their magnitude and phases are used to digitally calculate real, reactive and complex power in the line.